Combined Suspensory and Aperture Fixation of Posterior Tibialis Tendon Anterior Transfer for Dropfoot. Issue 4 (22nd October 2020) - Ray, Robbie; Navratil, Richard; Ogilvie, Andrew; Lewis, Thomas L.
Category: Other; Trauma Introduction/Purpose: Anterior transfer of the tibialis posterior tendon (TPT) can restore ankle dorsiflexion in patients with foot drop. A limitation of this procedure is the need for postoperative ankle immobilisation. We present the results of a novel dual method of TPT docking which infers immediate stability, allowing early weightbearing. Methods: 8 patients underwent 9 tendon transfers, age range of 28-52 years. 3 patients had dropfoot from common peroneal nerve injury, 6 cases were part of a complex cavovarus or spastic equinovarus correction. The TPT is passed to the dorsum of the foot through the interosseous membrane. The docking site is prepared with a bicortical pilot hole followed by unicortical overreaming. The TPT is whipstitched and an Arthrex biceps button is threaded to the sutures. The button is passed bicortical and flipped using a tension slide technique give stable suspensory fixation. Additional stability is conferred by overpassing an Arthrex biotenodesis screw giving aperture fixation. Patients are immobilised in a boot and allowed to weightbear immediately. Results: Follow up was 6 months. There was difficulty in docking of suspensory fixation in two of the early cases. These patients had aperture fixation and were immobilised non weightbearing in a cast for 6 weeks. With technical modifications, all subsequent patients had dual fixation. At 6 months there were no radiological or clinical failures of fixation. Patients without other underlying issues were able to mobilise splint free at 6 months. All patients were satisfied with their procedure. Conclusion: Aperture fixation with an interference screw has become the gold standard for TPT transfer, however, patients still need a prolonged period of immobilisation. Combined suspensory and aperture fixation is technically straightforward and seems to give more initial stability allowing early weightbearing. Further prospective studies and biomechanical studies are needed to validate this technique.